The fraud triangle – an alternative approach. Issue 3 (13th October 2021) - Kagias, Paschalis; Cheliatsidou, Anastasia; Garefalakis, Alexandros; Azibi, Jamel; Sariannidis, Nikolaos
Abstract : Purpose: In recent years, Public Accountability and Integrity have been matters of growing attention, both in the public and private sector, as citizens demand value for money entrusted to the governments through their taxes. In addition, in many countries, after the recent recession, government budgets and corporate returns have been reduced. Many corporate scandals have occasionally become known and have had a great impact on confidence in the market. Even worse, after the pandemic of COVID-19, «bare and exacerbated massive preexisting problems in the world's economic, social and security order, threatens to push up to 100 million people into extreme poverty in 2020, struck at a time of dwindling trust in representative governance» (UNDP, 2020). The funds of organizations in the private and public sector have been shrinking, whereas the situational pressures of fraud are increased. In this context, Dorris, President and CEO of the ACFE warns for explosion of fraud in the coming years and reminds that during the 2008 economic, companies cut-off, non-revenue generating activities, such as the internal audit and the compliance departments leaving them exposed to fraud. Therefore, organizations have to do more with less. The purpose of this paper is to present the development of the fraud theory on the management's perspective aiming to contribute to the efficient development of anti-fraud mechanisms Design/methodology/approach: Having identified the fraud theory developed so far, we provide a framework for the fraud risk management. Findings: This paper incorporates cost/benefits considerations, practical considerations and empirical evidence on fraud. Originality/value: This paper provides valuable information to enable the management, who has the primary responsibility to prevent and detect fraud, to disclaim responsibility by broadening their understanding of fraud theory.